Micro-dynamics of knowledge: actors, processes and territorial organization - Simone Strambach (Philipps-University Marburg, Department of Geography, 2013)
By applying the evolutionary economic geography approach and focusing on the organizational dimension of the knowledge-based theory of the firm the paper intends to make both a conceptual and an empirical contribution to understand the ways in which knowledge dynamics unfold in time and space and lead to innovative change. The article focuses on the connections of cumulative and combinatorial knowledge dynamics at the micro level of firms and other organizations. The empirical results base on the quantitative and qualitative meta-analysis of case studies in Europe that were obtained by the instrument of innovation biographies.
Keywords: D83; O4; O31; O32; R11; 330; Micro-dynamics of Knowledge; Innovation; Institution; territorial Organization